2017
DOI: 10.1080/13546805.2017.1322502
|View full text |Cite
|
Sign up to set email alerts
|

Associations of NEUROD2 polymorphisms and change of cognitive dysfunctions in schizophrenia and schizoaffective disorder after eight weeks of antipsychotic treatment

Abstract: Our findings suggest that the NEUROD2 gene could play a role in the pathophysiology of neurocognitive dysfunctions as well as in the change of cognitive symptoms under antipsychotic treatment in schizophrenia and schizoaffective disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…We identified PTSD-associated CpGs in genes implicated in other neuropsychiatric disorders (e.g. AGBL1, ATP9A, FLJ46321, GOT2, HOXA3, MAP7, and NEUROD2) [40][41][42][43][44][45] , which may provide insight into comorbidities commonly reported in PTSD. We also identified CpGs in genes that are involved in other epigenetic mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We identified PTSD-associated CpGs in genes implicated in other neuropsychiatric disorders (e.g. AGBL1, ATP9A, FLJ46321, GOT2, HOXA3, MAP7, and NEUROD2) [40][41][42][43][44][45] , which may provide insight into comorbidities commonly reported in PTSD. We also identified CpGs in genes that are involved in other epigenetic mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of this study also suggest that behavioral deficits in social behavior, which are reminiscent of autistic disorders, can be found in Neurod2 mutant mice. In addition, Spellman et al identified a direct association of NEUROD2 gene polymorphisms with changes in cognitive functions present in schizophrenic patients treated with antipsychotic drugs (Spellmann et al, 2017 ). It has also been shown that the lateral and basolateral amygdala nuclei fail to form in Neurod2 mutant mice, and that these mice display deficits in emotional learning (Lin et al, 2005 ).…”
Section: Neurod Genes In Human Neurological Disordersmentioning
confidence: 99%
“…Neurod2 knockout animals exhibit morphological and physiological defects in various brain regions, including thalamocortical connections, hippocampal synaptogenesis, axonal guidance of callosal axons, development of amygdalar nuclei, cortical fasciculation, targeted axogenesis of compact fiber tracts as well as differences in intrinsic excitability during cortical development (Olson et al, 2001;Lin et al, 2005;Ince-Dunn et al, 2006;Wilke et al, 2012;Bormuth et al, 2013;Chen et al, 2016). Accordingly, disruption of NeuroD2 function has been implicated in several neurodevelopmental, neuropsychiatric and mood disorders, such as autism (Runge et al, 2020), depression (Bagot et al, 2016), schizophrenia (Spellmann et al, 2017), or epilepsy (Sega et al, 2019).…”
Section: Introductionmentioning
confidence: 99%